TESTICULAR ABSCESS CAUSED BY SALMONELLA PARA-TYPHI - Nawaz, Nawaz G; Rehman, Rehman A; Muhammad, Muhammad S; Khawaja, Khawaja MA; Raja, Raja N; Aan, Aan N; Hussain, Hussain I; Akhter, Akhter S (Journal of Ayub Medical College Abbottabad, 2011)
This case is the first report of a bacteriologically proven testicular abscess in a child caused by Salmonella paratyphi ’˜A’ in Pakistan that clinically simulates a testicular tumour. The case also emphasises that a course of 2 weeks antibiotic is sufficient for testicular abscess if complete surgical debridement is done. Keywords: Salmonella paratyphi ’˜A’, Testicular Abscess, Tumour